2017
DOI: 10.3847/1538-4357/aa61f9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mass and Velocity Field in the Cosmic Web: Comparison Between Baryonic and Dark Matter

Abstract: We investigate the evolution of cosmic web since z = 5 in grid based cosmological hydrodynamical simulations, focusing on the mass and velocity field of both baryonic and cold dark matter. The tidal tensor of density is used as the main method for web identification, with λ th = 0.2 − 1.2. The evolution trends in baryonic and dark matter are similar, while moderate differences are observed. Sheets appeared early and their large scale pattern may have been set up by z = 3. In term of mass, filaments superseded … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
10
24
0
Order By: Relevance
“…For the same classification threshold λ th and smoothing length RG (see Subsection 2.2), comparison to Forero-Romero et al (2009) indicates that the mass fraction of knots at redshift z = 0 in Illus-trisTNG is higher by a factor ∼ 2 with respect to that in dark matter only simulations. On the other hand, the mass fraction of filaments in IllustrisTNG is similar to that of the dark matter simulations of Zhu & Feng (2017) show the evolution of mass and volume fractions of the four cosmic structures identified with the same method with λ th = 0.2 and 0.4, which bracket our fiducial value λ th = 0.3, but they adopt smaller smoothing lengths RG 390 kpc/h. Furthermore, the simulations of Zhu & Feng (2017) include baryons, but they use a different set of cosmological parameters (WMAP5).…”
Section: Dark Matter + Baryons Mass and Volume Fractions Of Cosmic Stsupporting
confidence: 82%
See 1 more Smart Citation
“…For the same classification threshold λ th and smoothing length RG (see Subsection 2.2), comparison to Forero-Romero et al (2009) indicates that the mass fraction of knots at redshift z = 0 in Illus-trisTNG is higher by a factor ∼ 2 with respect to that in dark matter only simulations. On the other hand, the mass fraction of filaments in IllustrisTNG is similar to that of the dark matter simulations of Zhu & Feng (2017) show the evolution of mass and volume fractions of the four cosmic structures identified with the same method with λ th = 0.2 and 0.4, which bracket our fiducial value λ th = 0.3, but they adopt smaller smoothing lengths RG 390 kpc/h. Furthermore, the simulations of Zhu & Feng (2017) include baryons, but they use a different set of cosmological parameters (WMAP5).…”
Section: Dark Matter + Baryons Mass and Volume Fractions Of Cosmic Stsupporting
confidence: 82%
“…On the other hand, the mass fraction of filaments in IllustrisTNG is similar to that of the dark matter simulations of Zhu & Feng (2017) show the evolution of mass and volume fractions of the four cosmic structures identified with the same method with λ th = 0.2 and 0.4, which bracket our fiducial value λ th = 0.3, but they adopt smaller smoothing lengths RG 390 kpc/h. Furthermore, the simulations of Zhu & Feng (2017) include baryons, but they use a different set of cosmological parameters (WMAP5). These differences influence the exact values of the mass and volume fractions of each structure.…”
Section: Dark Matter + Baryons Mass and Volume Fractions Of Cosmic Stsupporting
confidence: 82%
“…These results were based on our own Cosmic Web classification tool based on the deformation tensor of the density field (i.e. its Hessian matrix; Aragón-Calvo et al 2007;Hahn et al 2007;Sousbie et al 2009;Forero-Romero et al 2009;Zhu & Feng 2017;Cui et al 2018). This method assigns a physically-based web class to each region of the simulation at each redshift.…”
Section: Cosmic Web Classificationmentioning
confidence: 99%
“…In addition, the fraction of halos with t cool,cir > t H is relatively higher in filaments than other morphological types of cosmic structures. The rapid growth of this fraction since z = 2 is actually in accordance to the dramatic rising of filaments during the same epoch (e.g., Zhu & Feng 2017). Low mass halos in the filaments may witness relatively stronger reduction of gas accretion due to preheating.…”
Section: Baryon Fraction Environment Quenching and Large Scale Confomentioning
confidence: 62%
“…The threshold of eigenvalues is set to 0.8. The same method and threshold were applied in Zhu & Feng(2017), which showed that the dominant structures measured by mass fraction had transited from sheets to filaments at z ∼ 2 − 3.…”
Section: Simulations and Cosmic Web Classificationmentioning
confidence: 99%